Sentience - Koutsomichalis, Marinos (My University, 2021)
A speculative ‘infra-instrument’ prototype, that transmits a message (a poetry excerpt) is in Morse code. Poetry, then, transliterates to embodied rhythm: to loud low-frequency pulses that make a performance space and any bodies within it physically resonate accordingly.